Plant life form determines spatiotemporal variability and climate response of plant seed rain in subtropical forests - Yuyang Xie; Zehao Shen; Xuejing Wang; Liu Yang; Jie Zhang (Forest Ecosystems, 2024)
Spatiotemporal variation of seed rain reflects the response of plants in terms of their reproductive strategy to environmental gradients. In this study, we collected seeds from four sites in the Dalaoling Nature Reserve, Hubei Province, China, between 2011 and 2014, measured seed output and seed mass as seed rain traits, and compared their interannual and elevational variation. Then, we ran phylogenetic generalized mixed linear models (PGLMMs) to explore the effects of temperature and precipitation as well as interspecific differences on seed rain, and fitted the best regression models for seed rain vs. weather of canopy and understory species. The results showed no correlation between values of seed output and seed mass. However, the variation of the two traits showed significantly positive correlation. Seed output of canopy species generally decreased with increasing elevation, and showed significant interannual difference; however, seed output of understory species and seed mass for both canopy and understory species did not show consistency tends along elevational or in interannual variation. Seed output was significantly affected by temperature and precipitation, while seed mass mainly varied due to interspecific differences. Weather explained more the variation of the seed output of canopy species than that of understory species, with R2 values of 43.0% and 29.9%, respectively. These results suggested that canopy plants contributed more to the reproductive dynamics of the whole communities, and the canopy's buffer effect on the underground weakened the response of understory plants to weather variation in terms of their reproductive strategy.